Retained Endoloop ligature plastic tube, an unusual complication post appendicectomy - Bricknell, Lana; Goh, Ian Y.; Lewin, Joel; Siriwardhane, Mehan (International Surgery Journal, 2025)
Laparoscopic appendicectomies are one of the most common emergency operations. The use of ligatures is considered a safe technique for securing the appendiceal base. We describe a rare but important complication of this technique, with retention of the plastic tube from a polydioxanone (PDS) ligature in the abdominal cavity of a patient. A 64-year-old male presented with acute on chronic abdominal pain seven months following a laparoscopic appendicectomy. A CT demonstrated a bizarre linear tract extending from the bowel mesentery and right liver with associated pleural effusion. The patient underwent an exploratory laparoscopy, which identified a chronic peritonealised tract containing a plastic Endoloop® (Ethicon, Bridgewater, NJ, USA) sheath, traversing through the small and large bowel mesentery, through the right liver and diaphragm. The hard plastic tube was retrieved from the abdomen and the diaphragm repaired laparoscopically. The patient’s severe chronic pain resolved immediately postoperatively. The use of Endoloop® ligatures provides a simple and affordable method for appendiceal stump closure. Notably in many Australian hospitals, the Endoloop® plastic sheaths are not part of the final instrument count in an appendicectomy. Retention of the plastic ligature tube is a rare complication, with the literature only reporting one other case of this occurring following a cholecystectomy. This rare case of retention of the Endoloop® plastic sheath led to significant pain and morbidity and a second operation in this patient. This is the first reported case of this complication in the literature following an appendicectomy.